Education on the Impact of Disease Attacks on Horticultural Plants in Helumo Village, Suwawa District, Gorontalo Province. - Mayasari Yamin; Indah Puspitasari; Sri Nur Qadri (MALLOMO: Journal of Community Service, 2025)
Horticultural crops are commodities with high economic value, but they are highly susceptible to attacks by plant pests (OPT) in the form of pests and diseases. OPT attacks on horticultural commodities have been reported to cause significant yield losses, even leading to crop failure if not properly controlled. This community service program aims to improve early disease detection capabilities, implement better cultivation technologies, and ultimately reduce losses due to disease attacks. The community service program uses a socialization/educational lecture method combined with discussions, questions and answers, and field assistance. The results of this community service program have positively impacted farmers' knowledge and skills in recognizing early disease symptoms, understanding the causal factors, and being able to apply appropriate cultivation technologies.